CLINICOPATHOLOGICAL AND SURGICAL CHARACTERIZATION OF OPTIC NERVE-ASSOCIATED ATYPICAL MENINGIOMAS DEVELOPED IN THE ANTERIOR AND MIDDLE CRANIAL FOSSA - Claudia Florida Costea; Laurentiu Andrei Blaj; Dana Mihaela Turliuc; Vlad Liviu Hartie; Amelian Madalin Bobu; Andrei Ionut Cucu (Romanian Journal of Oral Rehabilitation)
Meningiomas developing in the anterior and middle fossa can compress the optic nerve (ON) and cause secondary visual disturbances. The aim of this study was to evaluate the clinical, pathological, and surgical characteristics of atypical meningiomas (WHO grade II) compressing the ON and located in the anterior and middle fossa of the skull base. Materials and Methods: We retrospectively studied the data of 5 patients with atypical meningiomas compressing the ON, diagnosed at the Prof. Dr. Nicolae Oblu Emergency Clinical Hospital in Iași, from 2010 to 2019. Results: Out of 5 patients, 4 presented with intracranial hypertension syndrome at admission, and 2 with motor deficits. Most patients (4 out of 5) had reduced visual acuity (VA) at admission, and 3 of them had partial or total ON atrophy. The preferred surgical approach was the pterional approach for sellar and parasellar meningiomas (2 cases), and the frontotemporal approach for large meningiomas with extension (3 cases). Conclusion: Although most patients had reduced VA at the time of admission, they presented to the hospital with other neurological symptoms. This suggests that the slow growth of intracranial meningiomas and the gradual compression of the ON may delay early diagnosis and, more importantly, effective treatment in these patients. We recommend regular evaluation of VA, as early detection of a slow-growing intracranial tumor, such as a meningioma, can help prevent vision loss.